Thrombin-Induced Platelet Factor Va Formation in Patients with a Gray Platelet Syndrome - Baruch, Dominique; Lindhout, Theo; Dupuy, Evelyne; Caen, Jacques P (Thrombosis and Haemostasis, 1987)
The present study was initiated to establish the functional factor V concentration in platelets of patients with a mild bleeding disorder ascribed to a gray platelet syndrome. This inherited platelet disorder has been characterized by a specific deficiency of alpha-granules and subsequent deficiencies in the alpha-granule proteins. We found that the concentration of plasma factor V was slightly decreased (70% of normal values). In contrast, platelet factor Va formation was severely impaired. Besides a much lower factor V content than in control platelets (10-20% of normal), the dependency of platelet factor Va formation on tlnumbin concentration was altered. Increasing the thrombin concentration 4-lold compared to the concentration that results in maximal factor Va generation from normal platelets did not result in a maximal factor Va formation from gray platelets. When a suspension of washed gray platelets was incubated with a prostacyclin analogue prior to the stimulation with thrombin, a 10-fold lower factor VQ activity was measured. Thus, thrombin-induced factor Va formation in a suspension of gray platelets is the result of a release reaction, followed by the thrombin-catalyzed activation of released factor V. Whereas the kinetics of the former reaction are apparently impaired, the kinetics of the latter one were found to be identical to those observed for normal platelet and plasma factor V activation.
Keywords: Gray platelet; Factor Va formation; Thrombin